Mr. Quiet - Hargreaves, Roger (London : Egmont, 2009)
Mr. Quiet is afraid of loud noises. This is a big problem for him, since he lives in Loudland. But one day he gets a letter from Mr. Happy inviting him to Happyland, where he finds - what else? - happiness!
Keywords: Children's stories